Recuperative Amino Acids Separation through Cellulose Derivative Membranes with Microporous Polypropylene Fiber Matrix - Aurelia Cristina Nechifor; Andreia Pîrțac; Paul Constantin Albu; Alexandra Raluca Grosu; Florina Dumitru; Ioana Alina Dimulescu (Nica); Ovidiu Oprea; Dumitru Pașcu; Gheorghe Nechifor; Simona Gabriela Bungău (Membranes, 2021)
The separation, concentration and transport of the amino acids through membranes have been continuously developed due to the multitude of interest amino acids of interest and the sources from which they must be recovered. At the same time, the types of membranes used in the sepa-ration of the amino acids are the most diverse: liquids, ion exchangers, inorganic, polymeric or composites. This paper addresses the recuperative separation of three amino acids (alanine, phe-nylalanine, and methionine) using membranes from cellulosic derivatives in polypropylene ma-trix. The microfiltration membranes (polypropylene hollow fibers) were impregnated with solu-tions of some cellulosic derivatives: cellulose acetate, 2-hydroxyethyl-cellulose, methyl 2-hydroxyethyl-celluloseand sodium carboxymethyl-cellulose. The obtained membranes were characterized in terms of the separation performance of the amino acids considered (retention, flux, and selectivity) and from a morphological and structural point of view: scanning electron microscopy (SEM), high resolution SEM (HR-SEM), Fourier transform infrared spectroscopy (FT-IR), energy dispersive spectroscopy (EDS) and thermal gravimetric analyzer (TGA). The re-sults obtained show that phenylalanine has the highest fluxes through all four types of mem-branes, followed by methionine and alanine. Of the four kinds of membrane, the most suitable for recuperative separation of the considered amino acids are those based on cellulose acetate and methyl 2-hydroxyethyl-cellulose.